Dual-factor loaded functional silk fibroin scaffolds for peripheral nerve regeneration with the aid of neovascularization. Issue 9 (19th January 2016) - Liu, Qiangqiang; Huang, Jianwen; Shao, Huili; Song, Lujie; Zhang, Yaopeng
Abstract : Dual-factor loaded functional silk fibroin scaffolds enhanced peripheral nerve regeneration with the aid of neovascularization. Abstract : To improve the therapeutic effect of a damaged peripheral nerve, aligned scaffolds based on regenerated silk fibroin (RSF) were fabricated by electrospinning, and were simultaneously loaded with dual factors of brain-derived neurotrophic factor (BDNF) and vascular endothelial growth factor (VEGF). An ELISA assay measurement in vitro demonstrated that the release of dual factors from the scaffolds was well maintained up to 2 weeks. Schwann cell (SC) morphologies on the RSF scaffolds were obtained using scanning electron microscopy (SEM) and laser scanning confocal microscopy (LSCM) after cell seeding. Cell viability and proliferation on the scaffolds were investigated using an MTT assay. Furthermore, the scaffolds were implanted in a mouse model to support nerve regeneration and angiogenesis in vivo, which was evaluated by histological and immunohistochemical (IHC) analyses at 4 and 8 weeks after implantation. In all retrieved scaffolds, de novo innervation and vascularization, indicated by a positive endothelial marker (von Willebrand factor, vWF) and an innervation marker (S-100 protein), were evident without chronic inflammatory responses. Compared to the control group, the dual-factor loaded scaffolds significantly promoted nerve regeneration and possessed great potential in peripheral nerve repair and regeneration, and for the repair of other tissues.